The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1177/102490790801500307
|View full text |Cite
|
Sign up to set email alerts
|

Hazmat Emergency Preparedness in Hong Kong: What are the Dangerous Goods in Kowloon?

Abstract: Hazmat emergency preparedness is critical, especially as Hong Kong prepares for major international events, such as the 2008 Olympic Equestrian Games. No published medical study has described the identities and quantities of dangerous goods (DG) in the Kowloon area and listed what antidotes are needed for these DG. This study describes what hazardous materials are most common in Kowloon to prioritise emergency preparedness and training. Materials & methods: Design: A descriptive, cross-sectional study. Setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…5 Recent studies in 2008 have found that hazardous materials are present in many areas in Hong Kong and can be a threat to the health of Hong Kong residents if preparations are not adequate. 6,7 The role of emergency doctors in a CBRNE incident is essential in Hong Kong and many modern cities worldwide. 8,9 With special expertise and presumed responsibility, emergency doctors must possess not only the knowledge, but also the readiness, to handle a sudden event of potential mass destruction.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent studies in 2008 have found that hazardous materials are present in many areas in Hong Kong and can be a threat to the health of Hong Kong residents if preparations are not adequate. 6,7 The role of emergency doctors in a CBRNE incident is essential in Hong Kong and many modern cities worldwide. 8,9 With special expertise and presumed responsibility, emergency doctors must possess not only the knowledge, but also the readiness, to handle a sudden event of potential mass destruction.…”
Section: Introductionmentioning
confidence: 99%